Predictors of progression in patients presenting with minor subcortical stroke. (24th March 2015) - Nannoni, S.; Del Bene, A.; Palumbo, V.; Petrone, L.; Sottile, F.; Pracucci, G.; Inzitari, D.
<x xml:space="preserve">Abstract</x> Objectives Early neurological worsening is common in minor subcortical strokes (SS) and may lead to a poor outcome. We aimed to describe clinical and imaging features associated with progression. Material and methods Consecutive patients with SS were divided into progressive and non‐progressive. Progression was defined as an increase of NIHSS motor score ≥1 point within 72 h from onset. Vascular risk factors and imaging features (vascular territory, size and number of slices in which the lesion was visible, the presence of leukoaraiosis) were compared in the two groups. We investigated potential independent determinants of progression using stepwise logistic regression. Results Thirty of 94 patients (31.9%) underwent progression. The distribution of vascular risk factors did not differ significantly between the two groups. Increasing number of risk factors was associated with a higher risk of progression (OR 2.2; 95% CI 1.1–4.5). Patients who progressed were more likely to have a lesion ≥15 mm in diameter (P = 0.004) or a lesion visible ≥3 slices (P = 0.007). After logistic regression stepwise adjustment for all the considered potential determinants, diameter ≥15 mm and severe leukoaraiosis proved to be independently associated with neurological worsening (OR = 6.3, 95% CI 2.0–19.6 and OR = 5.9, 95% CI 1.3–25.7, respectively). Conclusion In a series of consecutive SS, early neurological worsening was associated with a high vascular risk profile, a larger infarct size and the presence of severe leukoaraiosis. Based on the knowledge that extensive microvascular changes are a feature of severe leukoaraiosis, we hypothesize that stroke progression could be promoted through an impaired compensatory flow in the penumbral area.